Palatal perforation after a long intubation period - (:unkn) unknown (My University, 2005)
Palatal perforation is a very rare condition which may be congenital or acquired. A case of palatal perforation after a long intubation period is presented. © Springer-Verlag 2005.
Keywords: Crohn's disease; Intubation; Palatal perforation